Ready to die [large type] - Jackson, Lisa (Jackson, Lisa. Selena Alvarez/Regan Pescoli novels., 2013)
One by one, he'll stalk them, then he'll squeeze the trigger, savoring the way each lifeless body crumples to the reddening snow. One down already. And then there were five . . .